PENGEMBANGAN LEMBAR KERJA SISWA (LKS) BERNUANSA ISLAMI DALAM PEMBELAJARAN MATEMATIKA - Handayani, Fitri; Andriani, Siska (JURNAL e-DuMath, 2019)
AbstractThe purpose of the research is to find out the feasibility of the contextual approach LKS in mathematics learning both by teachers and students. This type of research uses research and development (R & D) with the steps used. The steps taken are limited to seven stages, due to time constraints so the steps of the research according to Sugiono are not fully implemented. Sampling was carried out by MTs Assa'adah Cicurug. Data collection techniques were carried out using student response questionnaires and teacher response questionnaires. From the response test the teacher got a score of 3.57 with very interesting criteria. Then the field trial from the school conducted by the students' questionnaire responses obtained an average score of 3.4 with the number of students testing at MTs Assa'adah 32 with very interesting criteria. The results of the validation of material experts obtained an average score of 3.27 with good criteria. Validation of media experts gained an average score of 3.23 with good criteria. Validation of Islamic scholars gained an average score of 3.13 with good criteria. It can be concluded that Islamic LKS with contextual approach to SPLDV material is categorized as very feasible and interesting to be used in learning at the eighth grade junior high school / MTs level.Keywords: LKS has an Islamic nuance, Contextual, SPLDV